Comparative efficacy and safety of statins for osteoporosis: a study protocol for a systematic review and network meta-analysis - Wei Zhu; Nan Xiang; Guangwen Zhou; Mengxin Xiong; Yaojun Xue; Ali Deng; Zhangkui Tan (BMJ Open)
Introduction Osteoporosis (OP) is a prevalent skeletal disease with high mortality and morbidity, followed by acute and chronic back pain, severe spinal deformity and dysfunction. First-line drugs for OP work through antiresorptive or anabolic mechanisms. Although with good efficacy, these drugs still have certain limitations in clinical application due to delivery routes, medication cycles and cost issues. Nowadays, statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) appear to be potentially promising drugs for OP. Despite the controversy, previous studies have shown the efficacy of statins in treating OP. Other studies have further indicated that the therapeutic effect of OP in statin-treated patients is dose dependent. However, scientists have not yet reached a consensus on the use of statins for the treatment or which statin to choose first. This study aims to review the literature, ascertaining the relative efficacy and safety of statins for patients with OP using a Bayesian network meta-analysis.Methods and analysis We will systematically search the following databases: MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database, Chinese BioMedical Literature Database and preprint servers to include randomised controlled trials that compare different statins for treating OP. Primary outcomes are the incidence of overall fractures and bone mineral density changes. Secondary outcomes contain adverse effects and bone turnover markers. All items of this review will comply with the Cochrane Handbook, and the quality of evidence will be evaluated by Grading of Recommendations Assessment, Development and Evaluation. A traditional pairwise meta-analysis and the Bayesian network meta-analysis will be performed to compare the efficacy of different statins.Ethics and dissemination Ethical approval is not required since this is a protocol study for meta-analyses. Results will be submitted to a peer-reviewed journal.PROSPERO registration number CRD42021242619.Search dates From database inception to February 2022.